(3QSGdI aj GdehSjbis - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3bGd Ef UfGYI GdehSjbi JTJed Ydi LRFjf CMOgeG jSei GdJCdja hehVhYg GdfZeg s
(3BNQgG (B:s
(3GdCbGeg Ydi feW hGMO ef GdLfSjf eSJMSf , hJHOjdgG Edi GdeNJdaGJ GdeJVGOGJ CMSf hGddg GdJhajb s
(3Vef eLehY , JQJjHgG (B: (3ef U (B723 - (3U(B738s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B58 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdehSjbi hGdZfGAs